Influence of temperature on tensile flow and workhardening behaviour of modified 9Cr–1Mo steel. (2014) - Sakthivel, T.; Laha, K.; Nandagopal, M.; Mathew, M. D.
Abstract : Tensile true stress ( σ )–true plastic strain ( ϵ ) and workhardening behaviour of modified 9Cr–1Mo steel have been analysed using flow constitutive relationships proposed by Hollomon, Ludwik, Ludwigson, Swift and Voce for wide range of temperatures (300–1023 K) at a strain rate of 3×10 −4 s −1 . Relationship proposed by Voce has been found to describe stress–strain data adequately at all temperatures. Variation of instantaneous workhardening rate ( θ ) with stress ( σ ) displayed the two stage workhardening behaviour. It was characterised by a rapid decrease in the transient stage followed by gradual decrease in the stage III of workhardening. Three distinct regimes have been exhibited in the variation of workhardening parameters of constitutive relationships and workhardening rate with temperature. The decrease in flow stress and workhardening parameters with increasing temperature indicated the dominance of dynamic recovery at high temperatures. At intermediate temperature (523–723 K) plateau has been observed and considered to be one of the manifestation of dynamic strain aging (DSA). Tensile properties of the steel have been predicted well from the parameters of voce constitutive relationship.